Expression of Phosphodiesterase 4B cAMP-Specific Gene in Subjects With Cryptorchidism and Down's Syndrome - Salemi, Michele; Condorelli, Rosita A.; La Vignera, Sandro; Castiglione, Roberto; Salluzzo, Maria Grazia; Bonaccorso, Carmela M.; Vinci, Mirella; Bosco, Paolo; Romano, Carmelo; Campagna, Cristina; Romano, Corrado; Calogero, Aldo E. (Journal of clinical laboratory analysis, 2016)
Cryptorchidism represents a risk factor for infertility and germ cell testicular neoplasia. An increased rate of cryptorchidism has been reported in subjects with Down's syndrome. Cyclic nucleotide phosphodiesterases (PDEs) are important messengers that regulate and mediate a number of cellular responses to extracellular signals, such as neurotransmitters and hormones. PDE4B, cAMP‐specific (PDE4B) gene which maps to chromosome 1p31.3 appears to be involved in schizophrenia, chronic psychiatric illness, learning, memory, and mood disturbances. Expression of PDE4 enzymes have been studied in testes of cryptorchid rats. Expression of PDE4B protein examination showed marked degenerative changes in the epithelial lining of the seminiferous tubules. These findings led us to evaluate PDE4 mRNA expression in leukocytes of peripheral blood of five men with DS and cryptorchidism and eleven subjects with DS without cryptorchidism compared with healthy men (controls) by quantitative Real Time PCR (qRT‐PCR). This study showed that the PDE4B gene was downexpressed in men with DS and cryptorchidism compared to normal controls and DS without cryptorchidism. A lower expression of the PDE4B gene may be involved in the neurological abnormalities in subjects with Down's syndrome. Moreover, PDE4B gene may be involved in the testicular abnormalities of men with DS and cryptorchidism.